Zastosowanie zamortyzowanego kosztu w wycenie kredytów nieregularnych - Oleksyk, Piotr (Amortized Cost Application in Valuation of the Irregular Credits, 2005)
The article is devoted to new depiction of the irregular credits in bank’s accounts. Principles of assets and liabilities valuations fulfill very important role in bank’s accounts. The valuation on the one hand causes particular components value changes, on the other hand relates to financial results or changes revaluation capital. Evaluation according to amortized cost, taking interest rate into consideration, consist in presenting an account of transaction costs in time during contract period related to given economic instrument. The argument, that support new principles implementation , are deep changes in the structure of the bank" s profit and loss account in recent years. Change basis are de-creasing interest rates, which determine profits" interest.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 47-53